2022
DOI: 10.3390/antiox11020310
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Obesity Effects of Ecklonia cava Extract in High-Fat Diet-Induced Obese Rats

Abstract: Obesity is becoming a global epidemic as a result of high-calorie food intake and unhealthy lifestyles. Different marine plants, especially brown algae (Ecklonia cava), are traditionally used to treat different health-related issues. The study was carried out to investigate the anti-obesity properties of E. cava 70% ethanol extract. To evaluate the anti-obesity effect of E. cava, both in vitro and in vivo tests were performed. E. cava suppresses pre-adipocyte 3T3-L1 differentiation in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Assessment of food and energy intake was carried out according to previous method [ 22 ] with modifications, The animal’s body weight and food intake was measured once a week during the study. The diet intake in each cage was calculated as: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of food and energy intake was carried out according to previous method [ 22 ] with modifications, The animal’s body weight and food intake was measured once a week during the study. The diet intake in each cage was calculated as: …”
Section: Methodsmentioning
confidence: 99%
“…But the most outstanding one that provides an accurate picture of human obesity is the diet-induced obesity model, which is usually carried out with a high-fat diet [ 21 ]. Previous reports also indicated that the use of rats is more appropriate for monitoring body weight change which is a major indicator of obesity [ 22 ]. Evidence from previous studies showed that treatment of high-fat- diet-fed rats with extracts of Gnidia glauca [ 23 ], Morinda citrifolia [ 24 ] , Anthocleista vogelii [ 25 ] and Silybum marianum [ 26 ] displayed strong anti-obesity activities by reducing organo-somatic and atherogenic indices.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that onion and apple supplementation could be helpful in the prevention/treatment of hepatic steatosis in obese Zucker rats. In addition, different studies have reported that the intake of vegetable-enriched diets was associated with lowering effects in liver enzymes in rodent models [ 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rat diets were provided by XIETONG.ORGANISM Co., Ltd. Some studies found that the ethanol extract of plenty of plants has the function of treating hepatic steatosis (Abbas, Boby, Lee, Hong, & Park, 2022;Quan et al, 2022), but there is a lack of research on the treatment of obesity and liver steatosis with ethanol extract of Arctium lappa L root. Samples of 5 and 100 mg/kg•bw/day of ethanol extract of Arctium lappa L were used as the low monitoring dose and high monitoring dose respectively for the experiment.…”
Section: Animals and Experimental Designmentioning
confidence: 99%